Gestión de posicionamiento de la Industria Florícola asociada al Mag, del cantón Saquisilí a través de la identidad marcaria - Azuero Bravo, Jeymi Mariana (2023)
The main objective of this research work is to manage the positioning of the venture "The Fresh Natural" through brand identity and different design strategies. These strategies expand the market by showing the services offered by the enterprise, so that in this way the producers can generate income. According to the theme raised, the research is with a qualitative methodology; Interviews are conducted that collect information necessary for the optimal development of the brand. In this way, the following question arises: How does Graphic Design help to position small businesses at a national and international level? It is the graphic design that directly helps the positioning of the ventures from the visibility that it provides to them. As a result of the investigation, graphic pieces were obtained such as: the corporate brand, the corporate identity manual, the product catalog, the web page design and brand animation.